Effect of perioperative dexmedetomidine on postoperative delirium in patients with brain tumours: a protocol of a randomised controlled trial - Zeng, Min; Zheng, Maoyao; Wang, Jie; Li, Shu; Ji, Nan; Peng, Yuming (BMJ open, 2024)
IntroductionNeurosurgery is a risk factor for postoperative delirium. Dexmedetomidine has a potential effect on reducing postoperative delirium. We aim to test the primary hypothesis that perioperative administration of dexmedetomidine reduces the incidence of postoperative delirium in patients undergoing neurosurgical resections of temporal glioma.MethodsThis is a single-centre, randomised, blinded and parallel-group controlled trial. A total of 366 patients will be randomised to either dexmedetomidine group (n=183) or placebo group (n=183). Subjects assigned to dexmedetomidine group will be given a continuous infusion at 0.4 µg/kg/h after anaesthesia induction until dural closure and then immediately receive an infusion of dexmedetomidine at 0.08 µg/kg/h by intravenous analgesia pump during the first 48 hours postoperatively. Patients in the placebo group will be given comparable volumes of normal saline, and intravenous analgesia pumps contain equal amounts of sufentanil and antiemetics, but no dexmedetomidine. The primary outcome is the incidence of postoperative delirium, which will be assessed with the Confusion Assessment Method two times per day during the first five postoperative days.Ethics and disseminationThe protocol (V.1.1) has been approved by the medical ethics committee of Beijing Tiantan Hospital, Capital Medical University (KY2023-186-02). The findings of this study will be disseminated through presentations at scientific conferences and publication in peer-reviewed journals.Trial registration number NCT06164314.